Computational study of hemodynamics analysis between mri measurement and cfd simulation on segmented patient-specific cerebral aneurysm model - Lim, Sheh Hong (2021)
The implementation of computational fluid dynamics (CFD) analysis was extensively performed to investigate the hemodynamics using segmented patient-specific cerebral aneurysm model geometry reconstructed from a medical image in this research. According to previous studies, the low-resolution magnetic resonance imaging (MRI) medical image produces a high measurement error and leads to inaccurate hemodynamics approximations with a large velocity difference of approximately 40 % between MRI measurement and CFD simulation. Besides, setting patient-specific boundary conditions before CFD analysis is critical, but there is no unified rule, especially for the setup of model geometry with bifurcation, which requires multiple outlet boundaries. Therefore, this study investigated the extracted model geometry with different threshold coefficients,